Avaliação das alterações condilares após cirurgia ortognática através de superposição regional com tomografia computadorizada - Claus, Jonathas Daniel Paggi (2018)
Purpose: The aim of the present study was to use cone-beam computed tomography (CBCT) regional superimposition to investigate the effect of bimaxillary advancement orthognathic surgery on condylar remodeling of the temporo mandibular joint (TMJ). Materials and Methods: Using a retrospective study design, 56 condyles from 28 healthy patients (age from 16 to 50 years) with mandibular retrognathism treated with bimaxillary advancement had CBCT scans taken pre-operatively and at an average 14 months postoperatively. Pre- and post-surgical scans were superimposed using regional and automated voxel-based registration to assess condylar changes in the follow-up period. The linear alterations were measured in six different areas of each condyle to assess the pattern of condylar remodeling. Results: Although no significant correlation was observed between changes in condylar surfaces, bone resorption occurred predominantly in the posterior and superior region, while bone formation was predominantly in the anterior surface. Medial and lateral surfaces presented fewer bone changes. The overall bone changes were smaller than 1mm in 48 condyles (85,7%) in 21 patients (75%). Conclusions: The results of this study suggest the hypothesis that alterations occurring in TMJ after performing orthognathic surgeries occur similar to an adaptive response, especially in healthy patients, other than a pathological or inflammatory process. Other studies with similar methodologies may clarify the mechanisms involved in cases where the process of condylar remodeling is more present.